Implementasi Kebijakan Pengelolaan Sampah Daerah Kabupaten Sidoarjo - Ruddy Oktarino (Jurnal Administrasi Publik, 2017)
The result of this research is dedicated for see the policies of Sidoarjo Government in improving the participation of the community to manage waste become economically valuable goods and can be reused effectively. However, the policy have not been able to fix the number of the volume of trash in sidoarjo because the barriers follow up the process of the implementation. That barriers is come from internal and eksternal of the government agencies. Internal barriers is about there’s no strict sanctions for people who littering. Eksternal barriers is about a lack of awareness of each society about the importance of environmental issues and the high level of urbanization people come to Sidoarjo.